CLAY MINERAL EFFECTS ON LOW SALINITY WATER INJECTION MODELING AND SIMULATION AT BX STRUCTURE IN T-S FIELD - Zakyan, Hafizh
Low Salinity Water Injection (LSWI) is an alternative method which in the last decades has been considered quite promising as an enhanced oil recovery (EOR) application. LSWI is more simple, low cost and environmentally friendly compared to other EOR methods. The potential for increasing oil recovery trough LSWI method is reported to reach up to 5-22 % of the OOIP both from laboratory test results and field test results. Currently, there are 13 proposed mechanisms from various studies are declared as the main mechanism behind LSWI, in the case of sandstone reservoirs, it is known that the final effect of LSWI is the changes of rock wettability which initially prone to be oil-wet or mix-wet and becomes more water-wet after LSWI because of the process of releasing oil from the clay surface. The presence of clay minerals needs to be modeled comprehensively because it is closely related and the main key to predicting the response of the reservoir during the LSWI process. Thus, in this study an optimization of the mechanistic model approach of the implementation of LSWI in the reservoir by considering the presence of clay minerals which will be represented in the form of reservoir modeling and simulation using geological and reservoir data from the BX Structure in the T-S Field, South Sumatra. The results of the study shown that the LSWb (1,800 ppm) which is 10 times the dilution of HSW is the best injection rate scenario. with the addition of RF of 4.37% from HSW, the implementation of the heterogeneous Qv model also has an impact on oil recovery compared to the homogeneous Qv model, it is known that there is a difference in the RF margin range of 1.41 - 2.91%, in the other hand, effect of the distribution of clay mineral dispersion has a very dominant influence in reducing the quality of reservoir rock properties compared to laminar and structural distribution.